Mansfield park - Austen, Jane, 1775-1817. (Mumbai, India: Wilco International, 2022)
Mansfield Park follows ten-year-old Fanny Price, whose penniless family sends her to live with her wealthy relatives. Shy and ignored, Fanny is treated unkindly by her cousins, her two aunts, and her uncle. As Fanny grows up, scandals and tragedies plague the family. The story of a young woman trying to find her place in society, this classic coming-of-age story was revolutionary for its time - Amazon
Jane Austen (1775-1817) was born in Hampshire, England, to George Austen, a rector, and his wife, Cassandra. Her novels include Sense and Sensibility (1811), Pride and Prejudice (1813), Mansfield Park (1814), Emma (1815), and Northanger Abbey and Persuasion, published together posthumously in 1818. A short epistolary novella, Lady Susan, and another unfinished work, The Watsons, were publish posthumously in 1871, and a final unfinished novel, Sanditon, was eventually published in 1925. Her works are considered to be among the finest examples of early 19th century British literature, hallmarks of the transitionto 19th century literary realism.
Keywords: Young women -- Fiction; Children of the rich -- Fiction; Country homes -- Fiction